3D Optical Investigation of 2 Nail Systems Used in Tibiotalocalcaneal Arthrodesis: A Biomechanical Study. (May 2017) - Evers, Julia; Lakemeier, Martin; Wähnert, Dirk; Schulze, Martin; Richter, Martinus; Raschke, Michael J.; Ochman, Sabine
Background: Although retrograde intramedullary nails for tibiotalocalcaneal arthrodesis (TTCA) are an established fixation method, few studies have evaluated the stability of the available nail systems. The purpose of this study was to compare biomechanically the primary stability of 2 nail-systems, A3 (Small Bone Innovations) and HAN (Synthes), in human cadavers and analyze the exact point of instability in TTCA by means of optical measurement. Methods: In 6 pairs of lower legs (n = 12) of fresh-frozen human cadavers with osteoporotic bone structure, bone mineral density (BMD) was determined. Pairwise randomized implantation of either an HAN or A3 nail was executed. Performance and stability were measured by quasi-static tests using 3D motion tracking (NDI Optotrak-Certus) followed by cyclic loading tests during dorsi- and plantarflexion. Results: 3D optical analysis in quasi-static tests showed a significantly lower degree of movement for the HAN nail in rotational and dorsi-/plantarflexion, especially in the subtalar joint. Cyclic loading tests were consistent with quasi-static tests. Conclusion: The A3 nail offered lower stability during axial torsion in the ankle and subtalar joints and during plantar- and dorsiflexion in the subtalar joint in osteoporotic bones. This study was the first to examine the primary stability of different arthrodesis nails in TTCA and their bony parts with a 3D motion analysis. Clinical Relevance: The better stability of the locking-only HAN nail in this osteoporotic test setup could lead to more favorable results in comparison to the A3 nail in clinical use.